Malaria in Dengue Patients (Medical Forum Monthly, 2024)
Objective: To determine frequency of malaria in dengue patientsStudy Design: Cross sectional studyPlace and Duration of Study: The study was carried out in the Department of Medicine, Civil Hospital Karachi from June 2008 to December 2008.Materials and Methods: 274 dengue patients with Ig M antibody positive results were included in the study after informed consent Malaria parasite peripheral film and malarial ICT (immunochromatography) test of all these dengue patients were performed in order to detect the presence of co-infection with malaria. Age and sex of the patients were also noted.Results: In the study, out of 274 dengue patients, 189 (69%) were males and 85 (31%) were females. Mean age was 31.01± 14.83 years. 41 (15%) dengue patients had concomitant malarial infection. Out of these 41 dengue-malaria co-infected patients, 29 (10.6%) had plasmodium vivax; 8 (2.9%) had plasmodium falciparum and 4 (1.5%) had both falciparum + vivax.Conclusion: Patients with dengue fever are predisposed to have concomitant malarial infection. Hence, these must be investigated for malaria as undiagnosed and untreated malaria can increase the morbidity and mortality of the dengue patients.